2018
DOI: 10.3390/rel9020040
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Sense of Community in Faith Communities

Abstract: Previous studies have found that religion and spirituality (R/S) are related to less suicidal ideation (SI), fewer suicide attempts and fewer suicide deaths and that an absence of social support is associated with SI, suicide attempts, and suicide death. 745 Catholic, Jewish, and Protestant congregants completed an online survey measuring their sense of community (SOC) in their faith community, overall belonging and SI. SOC was weakly related to SI. Congregants attending more than one service per week reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…Perceived burdensomeness may be more important than thwarted belonging because "relationships cannot meet the need to belong when the interactions are characterized by perceptions of burdensomeness" (Van Orden et al 2012, p. 212). The finding that Groups One and Three reported less perceived burdensomeness than Group Two (who self-identified as not religious/atheist) is consistent with Mason et al (2018), who found that congregants who attended one or more faith community activities per week reported significantly less perceived burdensomeness.…”
Section: Discussionsupporting
confidence: 83%
“…Perceived burdensomeness may be more important than thwarted belonging because "relationships cannot meet the need to belong when the interactions are characterized by perceptions of burdensomeness" (Van Orden et al 2012, p. 212). The finding that Groups One and Three reported less perceived burdensomeness than Group Two (who self-identified as not religious/atheist) is consistent with Mason et al (2018), who found that congregants who attended one or more faith community activities per week reported significantly less perceived burdensomeness.…”
Section: Discussionsupporting
confidence: 83%
“…Some evidence suggests that the relationship between religiosity and low suicide rates is accounted for by the social support that comes from religious communities (Robins & Fiske, 2009). Among members belonging to varying religious communities, a higher sense of community was associated with increased belongingness and reduced suicidal ideation (Mason et al, 2018). Thus, the low levels of religiosity in the West could contribute to lacking a sense of community and feelings of isolation described above, thereby increasing suicidal ideation.…”
Section: Contextual Factorsmentioning
confidence: 99%